Analisis Miskonsepsi Siswa SMP pada Materi Fisika - Auli, Selly; Diana, Nirva; Yuberti, Yuberti (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstract: This study aims to determine and analyze the presence or absence of misconceptions experienced by students on the concept of vibration and wave matter. This research is a descriptive qualitative. Conducted on the students of class VIII. The sample used is taken by random sampling. The material used in analyzing misconceptions is the material that has been studied previously, the matter are vibration and waves. The instrument used is a reference concept map. This research is conducted through three stages, namely pre-survey stage, implementation, and conclusion. The data of the research are analyzed quantitatively and qualitatively. The results show that the average concept map in criteria is low. The low concept map is caused by the distribution of concept statement with the average of misconception 7.40%, and do not understand the concept of 61.59%, so the average students who understand the concept of 31.01%. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis ada atau tidaknya miskonsepsi yang dialami siswa pada konsep materi getaran dan gelombang. Jenis penelitian ini adalah deskriptif kualitatif. Penelitian dilakukan pada siswa kelas VIII. Sampel yang digunakan diambil secara random sampling. Penelitian ini dilakukan melalui tiga tahapan, yaitu tahap pra survey, pelaksanaan, dan penarikan kesimpulan. Data hasil penelitian dianalisis secara kuantitatif dan kualitatif. Hasil menunjukkan bahwa rata-rata peta konsep dalam kriteria rendah. Rendahnya peta konsep disebabkan karna sebaran pernyataan konsep dengan rata-rata miskonsepsinya 7.40%, dan tidak paham konsep 61.59%, sehingga rata-rata siswa yang paham konsep sebesar 31.01% .